Obstetric care provider's knowledge about the use of low dose aspirin for preeclampsia prevention in low and middle income countries: a systematic review and meta-analysis - Eyob Shitie Lake; Mulat Ayele; Befkad Derese Tilahun; Besfat Berihun Erega; Alemayehu Sayih Belay; Gizachew Yilak (BMC, 2024)
Abstract Introduction : Preeclampsia can elevate the likelihood of unfavorable consequences for a mother, such as severe morbidity and mortality. World Health Organization recommends low dose acetylsalicylic acid (aspirin, 75 mg per day) for the prevention of preeclampsia in women at moderate or high risk of developing the condition. The use of low dose aspirin is dependent on the knowledge of health care providers working in the antenatal care units. We found inconsistent figures regarding the knowledge level of health care providers on low dose aspirin for preeclampsia prevention around different low and middle income countries in the world. Thus, determining the pooled knowledge level of health care providers is very important. Methods This systematic review and meta-analysis (SRMA) was conducted on the knowledge level of among obstetric care providers towards preeclampsia prevention in low and middle income countries. We identified relevant literature in the English language only. A comprehensive search was conducted on databases such as PubMed, Google Scholar, HINARI, and Scopus. Subsequently, all datasets were exported to Mendeley reference manager and transferred to a Microsoft Excel spreadsheet to eliminate duplicate data during the review process. The extracted Microsoft Excel spreadsheet format data was imported to STATA software version 17 (STATA corporation, Texas, USA) for analysis. Then random effect model was used to estimate the pooled level of knowledge of health care providers on low dose aspirin for preeclampsia prevention in low income countries. Cochrane Q-test and I2 statistics were computed to assess heterogeneity among all the studies included in this SRMA. Result A total of 1231 articles were identified through our search strategies, including Google Scholar, PubMed, Hinari and Scopus. Ultimately, six articles met the eligibility criteria for inclusion in the final SRMA. The pooled knowledge level of healthcare providers regarding the use of low-dose aspirin for preeclampsia prevention in low-income countries was found to be 16.38% (95% CI: 4.36-28.40). The Cochrane heterogeneity index, with a substantial I2 value of 98.89% and a significant P-value of 0.01, indicated significant heterogeneity among the primary studies included. Conclusion the knowledge level of obstetric care providers in low and middle income countries is found very low and all the governmental and non-governmental organizations should strive to enhance the knowledge of obstetric care providers on the use of low dose aspirin for preeclampsia prevention in low and middle income countries.